Epidemiology and diagnostics of venous disease in Poland - Mateusz Curyło; Katarzyna Cienkosz; Marcin Mikos; Aleksandra Izabela Czerw (Kazimierz Wielki University, 2017)
Cardiovascular diseases are the leading cause of death in Poland. The percentage of people who die from cardiovascular disease is decreasing year by year, but adequate patient education and access to specialist physicians are still required. Chronic venous disease is one of the disorders of this system, whose probability of occurrence increases with age. Other risk factors include gender, type of occupation, obesity, eating habits and constipation, pregnancy, and genetic factor. The symptoms of the disease include: pain, lower limb edema, fatigue / leg pain, tingling, enlargement of the small blood vessels, enlargement and constriction of the subcutaneous veins, skin lesions, skin discolouration, itching of the skin of the legs, congestive dermatitis, ulcers. The degree of disease is determined using the CEAP scale. Prophylactic and early detection of disease results in shorter treatment times and reduced costs. Unfortunately, a large number of primary care physicians are skipping the physical examination of the lower limb, thus prolonging the diagnosis process and the patient being treated for a more advanced disease. Studies show that there is a difference in the incidence of chronic venous disease and the severity of the disease, depending on the province that has been affected. This may indicate the need to standardize nationwide training methods for doctors. The most common method of treatment is the combination of pharmacotherapy and compression therapy.